Synthesis of (Z)-Cinnamate Derivatives via Visible-Light-Driven E-to-Z Isomerization - Shu, Penghua; Xu, Haichang; Zhang, Lingxiang; Li, Junping; Liu, Hao; Luo, Yuehui; Yang, Xue; Ju, Zhiyu; Xu, Zhihong (SynOpen, 2019)
(Z)-Cinnamate derivatives are prevalent in natural bioactive products and in organic synthesis. Herein, we report a practical approach toward the efficient synthesis of (Z)-cinnamate derivatives via visible-light-driven isomerization. When E-isomers of cinnamate derivatives were irradiated with blue light in the presence of 1 mol% Ir2(ppy)4Cl2 (ppy = 2-phenylpyridine), Z-isomers were readily obtained in good yields. This strategy allows the large-scale synthesis of (Z)-cinnamate derivatives with simple purification. This convenient, mild, and green synthetic methodology was subsequently applied to the synthesis of coumarins.
Keywords: visible light; isomerization; Ir2(ppy)4Cl2; cinnamate; coumarins